Evaluation of the family-led MUAC component of an integrated package of interventions to reduce wasting in Chad and Mali - Diop, Loty; Becquey, Elodie; Diatta, Ampa Dogui; Touré, Mariama; Fall, Talla; Ouedraogo, Moctar; Sawadogo, Abdoulaye; Huybregts, Lieven (International Food Policy Research Institute, 2023)
• Family-led MUAC, where caregivers and other household members screen their own children regularly to detect child wasting early-on, is a promising strategy to boost screening coverage leading to more children with wasting to be referred and enrolled in available treatment services.